ANALISIS PENGARUH LOKASI, HARGA DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN DI SWALAYAN TWENTY TWO SUNGAI LIMAU - Wahyu Erdalina (Jurnal Ekonomi Sakti, 2018)
Abstract This study aims to determine 1) location of consumer satisfaction, 2) price of consumer satisfaction, 3) service to customer satisfaction at the Twenty-Two Supermarket in Sungai LimauNagariKuranjiHilir. The population in this study was the Two Twenty-Two Supermarket LimauNagariKuranjiHilir consumers who served 255 people. The sample in this study was the Twenty-two-storey Supermarkets of Sungai LimauNagariKuranjiHilir, which was honored by 100 people. With a non-probability sampling technique using accidental sampling. Data retrieval techniques in this study use a test tool used in questionnaires. The analysis technique used in this study is to use frequency distribution techniques. Based on the results of the study, a significant effect was found between the location, price, and service variables on the satisfaction of two-twenty-two self-service customers in Sungai LimauNagariKuranjiHilir. Significant service quality on customer satisfaction is 89.3% which states that a good location will have the opportunity to buy back 89.3 times compared to respondents who stated a bad location. The price has a significant effect on consumer satisfaction by 88.2%, which states that they will buy 88.2-fold repeat purchases compared to respondents who stated high product prices. Significant service to customer satisfaction is 88% of respondents who will serve repurchase 88 times compared to respondents who stated poor service.